0207 Impact of Changing School Start Times on Teachers/Staff. (12th April 2019) - Plog, Amy E; McNally, Janise; Wahlstrom, Kyla L; Meltzer, Lisa J
Abstract: Introduction: Delaying middle and high school start times is important for increasing sleep in students. However, no known studies have examined the impact of changing school start times on the personal sleep and well-being of K-12 teachers/staff in a district having made such a change. Methods: In Fall 2017, the Cherry Creek School District changed school start times at all levels: elementary school [ES]: from 9:00 to 8:00 a.m.; middle school [MS]: from 8:00 to 8:50 a.m.; high school [HS] from 7:10 to 8:20 a.m. Teachers and school-based staff completed online surveys in Spring 2017 (pre-change n=2287) and Spring 2018 (post-change n=2702). Questions included weekday bedtime [BT] and wake time [WT], with total sleep time [TST] calculated as the difference between WT and BT; engagement with family/friends (dinner, talking about day); and PROMIS Sleep Related Impairment (SRI). Results: Post-start time change, ES teachers/staff reported significantly earlier BT and WT (9m and 10m, ps <0.001), with no change in TST; MS teachers/staff reported no change in BT, with significantly later WT and longer TST (15m and 12m, ps <0.001); HS teachers/staff reported minimal change in BT, with significantly later WT and longer TST (28m and 21m, ps <0.001). No significant differences were found in SRI T-scores for ES or MS teachers/staff, but HS teachers/staff reported a significant decrease ( p <0.001). Significantly fewer ES teachers/staff felt prepared to start the day post-start time change (80 vs. 64%, p <0.001). Significantly fewer MS teachers/staff regularly had dinner with their family post-start time change (66% vs. 55%, p =0.002). No changes were found at any level for talking with family/friends about the day. Conclusion: Similar to MS/HS students, MS/HS teachers/staff reported a significant increase in sleep after delaying start time, with less daytime sleepiness in HS teachers/staff. ES teachers/staff reported feeling less prepared to start the day and MS teachers/staff had dinner with their family less frequently. Although adolescent sleep and well-being are the primary factors driving start time changes, it is important to consider how this policy impacts other members of the school community. Support (If Any): Robert Wood Johnson Foundation